The Relationship Of Giving Exclusive Breast Milk To The Growth Of Head Circumference And Body Length Of Baby Aged 6-12 Months At Puskesmas Air Tawar Of Padang 2024 - Yolanda, Usfia Rise; Sari, Fatmi Nirmala; Ririn, Ririn (Alifah Health Science Symposium Proceeding, 2024)
Based on data from the World Health Organization (WHO) in 2022, 200 million children did not reach their optimal developmental potential. One of the factors contributing to this growth hindrance is the low rate of exclusive breastfeeding for infants aged 0-6 months. The aim of this study is to examine the relationship between exclusive breastfeeding and the growth of head circumference and body length in infants aged 6-12 months. The type of research is quantitative analytical with a cross-sectional approach, involving a sample of 97 respondents aged 6-12 months. Data were collected using checklists and questionnaires, and statistical analysis was conducted using the chi-square test. The univariate analysis results were obtained from 97 respondents. Out of these, 65 babies (57.73%) received exclusive breastfeeding. Regarding the babies' length, 68 babies (70.10%) were of normal length, while 43 babies (44.32%) had a normal head circumference. The bivariate analysis revealed a significant relationship between exclusive breastfeeding and the growth of body length in babies aged 6-12 months, as indicated by a Chi-Square value with a p-value of 0.044, which is less than α = 0.05. However, there was no significant relationship between exclusive breastfeeding and head circumference in babies aged 6-12 months, as shown by a Chi-Square value with a p-value of 0.682, which is greater than α = 0.05. Exclusive breastfeeding is a crucial factor in the growth and development of infants into adulthood. Exclusive breastfeeding provides the necessary nutrition to support the baby's growth. It is important for mothers who have provided exclusive breastfeeding to continue paying attention to their baby's nutrition, especially regarding complementary foods, once the baby is older than 6 months.